Sprogsamfund, sprogpolitik og ordbøger - Svavarsdóttir, Ásta (LexicoNordica, 1994)
The article addresses general monolingual dictionaries of Icelandic in the light of two characteristics of the language community, its unusually smal! size (265.000 members), combined with a puristic trend in language policy, mainly reflected in a reluctance to accept loanwords. Due to size the market only allows a very limited number of dictionaries, and thus specialization is unrealistic, until now even though the needs are more or less the same as in a larger society. For example, only one monolingual dictionary of the modem language has been available. The general interest in language and language policy in the community makes questions on good usage a very topical part of Icelandic dictionaries, even though they are not easy to cope with as the answers are often a matter of taste. This is discussed at some length in the article, especially with respect to the selection of vocabulary in dictionaries, and to notes on usage and style.